Effects of inorganic and organic acid pretreatments on the hydrothermal liquefaction of municipal secondary sludge. (15th October 2018) - Liu, Renlong; Tian, Wenying; Kong, Shengyan; Meng, Yanghao; Wang, Huansheng; Zhang, Jinglai
Highlights: Various acid pretreatments were used in the hydrothermal liquefaction of sludge. Inorganic acid pretreatments had a better performance in improving bio-oil yield. A maximum bio-oil yield of 26.75 wt% was obtained from the HCl pretreatment. The HCl pretreatment resulted in higher HHV and hydrocarbon content. Abstract: In this study, the effects of inorganic (HCl, HNO3 and H2 SO4 ) and organic (HCOOH, CH3 COOH and HOOCCOOH) acid pretreatments on the hydrothermal liquefaction (HTL) of municipal secondary sludge (MSS) were investigated. The results showed that all acid pretreatments could increase bio-oil yield by changing the proportion of organic matters and ash content in feedstock and thus facilitating the conversion of water soluble product to bio-oil. A maximum bio-oil yield of 26.75 wt% was obtained from the HCl pretreatment which increased 7.5 wt% compared to the blank experiment. Moreover, the inorganic acid pretreatments showed a better performance in terms of enhancing bio-oil quality as their higher heating values (HHVs, 31.83–36.04 MJ/kg) were much higher than that from organic acid pretreatments (24.57–29.22 MJ/kg). The characterization analysis of bio-oil indicated that the HCl pretreatment was most beneficial for the formation of light fraction and increment of hydrocarbon.